Prongs or mask for nasal continuous positive airway pressure in neonates: which one is more comfortable - ÖZDEMİR, HÜLYA (My University, 2023)
Background: Nasal continuous positive airway pressure (NCPAP) is a common mode of respiratory support in neonatal intensive care units. Our objective was to compare whether NCPAP given with nasal prongs compared with a nasal mask reduces the pain scores in preterm infants with respiratory distress. Methods: Preterm infants on NCPAP due to respiratory distress were included in the study. All infants received NCPAP via the Infant Flow SiPAP. The COVERS pain scale was used to score the infants’ pain. Each infant was studied alternating between nasal prongs and a nasal mask. Heart rate, respiratory rate, oxygen saturation, and transcutaneous CO2 (tcCO2) were monitored. Blood pressure and the infants’ pain scores were determined every 30 minutes and the average of measurements was taken. Results: The median (interquartile range) values of pain scores, respiratory rates, oxygen saturations, tcCO2 levels, and systolic blood pressures differed significantly and favored the nasal mask. Conclusions: This study demonstrates that continuous positive airway pressure via a nasal mask leads to a significant reduction in pain scores without altering the respiratory parameters of babies. On the basis of this study, it is possible to conclude that NCPAP applied via nasal mask may be a good alternative to NCPAP applied via nasal prongs.
Keywords: NCPAP; preterm infants; nasal mask; nasal prongs; pain